(untitled) (Research, Society and Development, 2021)
Kefir is probiotic food that presents great potential for application and development of new products, because it is a raw material of easy preparation and low cost. In addition, its consumptions has several health-related benefits. The food market tries to meet the growing demand of the search for more nutritious foods. This new trend reinforces the incentive to develop functional foods. Therefore, the present work raised bibliographies on the development and acceptance of Kefir-based products in different Brazilian states. In recent years there was a significant increase in scientific papers related to the topic, mainly articles on flavoring kefir fermented in order to increase its sensory acceptance. This subclass occupied 45.71% of the articles analyzed and 97,14% of the products in which they were sensory evaluated presented good sensory acceptance. Minas Gerais was the state that stood out the most in the number of publications related to the development of new Kefir-based products, with 17.14% of publications. Therefore, despite Kefir being a little consumed product in Brazil, studies show a high sensory acceptance which encourages the development of new products based on it.